Effect of low‐dose proton pump inhibitor on preventing upper gastrointestinal bleeding in chronic kidney disease patients receiving aspirin. Issue 3 (March 2015) - Lim, Hyun; Kim, Jong Hyeok; Baik, Gwang Ho; Park, Ji Won; Kang, Ho Suk; Moon, Sung Hoon; Park, Choong Kee
Abstract Background and Aim Upper gastrointestinal bleeding (UGIB) leads to significant morbidity and mortality in chronic kidney disease (CKD) patients. This study determined the efficacy of using a low‐dose proton pump inhibitor (PPI) to reduce the risk of non‐variceal UGIB in CKD patients receiving aspirin. Methods We retrospectively reviewed the medical records of 500 CKD patients who received aspirin between January 2008 and March 2013. Cumulative incidence analysis using the Kaplan–Meier method was performed to analyze the rate of non‐variceal UGIB and association with the administration of low‐dose PPI. Results Of the 500 patients, 191 received low‐dose PPI. Over the follow‐up period, which lasted 1067 person‐years, three patients in the low‐dose PPI group (8.9 per 1000 person‐years) and 19 patients in the non‐PPI group (25.9 per 1000 person‐years) developed non‐variceal UGIB, respectively (P = 0.113). Low‐dose PPI use did not decrease the risk of UGIB in CKD patients, including patients who did not receive dialysis (P = 0.127). However, according to the subgroup analysis of 230 patients who received dialysis, the low‐dose PPI group (14.4 per 1000 person‐years) demonstrated significantly reduced incidence and risk of non‐variceal UGIB in comparison with the non‐PPI group (53.8 per 1000 person‐years) (P = 0.032). Conclusion Prophylactic low‐dose PPI can reduce the risk of non‐variceal UGIB in dialysis patients receiving aspirin.